Measurement of exclusive γγ → W+W− production and search for exclusive Higgs boson production in pp collisions at √ s = 8 TeV using the ATLAS detector - Aaboud, M. (2016)
Searches for exclusively produced W boson pairs in the process pp(γγ) → pW+W− p and exclusively produced Higgs boson in the process pp(gg) → pH p have been performed using e ±µ ∓ final states. These measurements use 20.2 fb−1 of pp collisions collected by the ATLAS experiment at a center-of-mass energy √ s = 8 TeV at the LHC. Exclusive production of W+W− consistent with the Standard Model prediction is found with 3.0σ significance. The exclusive W+W− production cross-section is determined to be σ(γγ → W+W− → e ±µ ∓X) = 6.9 ± 2.2(stat.) ± 1.4(sys.) fb, in agreement with the Standard Model prediction. Limits on anomalous quartic gauge couplings are set at 95% confidence-level as −1.7×10−6 < a W 0 /Λ 2 < 1.7×10−6 GeV−2 and −6.4×10−6 < a W C /Λ 2 < 6.3×10−6 GeV−2 . A 95% confidence-level upper limit on the total production cross-section for exclusive Higgs boson is set to 1.2 pb.